Micro-mechanics of interfacial debonding: demolding of hot-embossed polymeric microfluidic substrate - Jeffry William Tani (2015)
Hot-embossing is one well-known micro-molding technique to fabricate the highly potential polymeric microfuidic devices. During the process, demolding which involves separation of polymer substrate from the mold is one crucial factor in determining the success of replication, because demolding defects are extremely prone to occur. This thesis aims to develop an in depth understanding in the demolding mechanics of the hot-embossed polymeric substrate based on analytica~experimental and numerical studies in order to facilitate successful and efficient mass production of the microtluidic devices. An understanding of the previously unknown main demolding-failure mechanism is also established. In addition, the influence of eight essential parameters on the demolding process and demolding failure has also been systematically studied. With the developed understanding of each parameter, it has been demonstrated that optimal processing conditions to achieve successful and efficient replications can be eventually accomplished. Moreover, the findings can also be readily utilized to provide optimal processing and design guidance for industrial application of polymer micro-molding as well as other novel replication processes.